Cushion rubber composition with high fatigue performance as well as preparation method and application thereof
By adjusting the structure and composition of N326 carbon black and combining it with hydrazide compounds to form stable cross-links, the problem of insufficient fatigue performance of all-steel radial tire cushion rubber was solved, thereby improving the tire's service life and safety.
Patent Information
- Application Number
- CN202510881343.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2025-09-19
- Estimated Expiration
- 2045-06-27
AI Technical Summary
The cushion rubber of existing all-steel radial tires has insufficient fatigue performance and is prone to defects such as interface delamination, stress crack expansion, and belt misalignment, which affect the tire's service life and safety.
By using high-precision/purity N326 carbon black in combination with hydrazide compounds, adjusting the compressed DBP oil absorption value, CTAB adsorption value and ash content of carbon black to form stable cross-linking bonds, combined with fine-tuning of other formula components, the fatigue performance of the pad rubber is improved.
Significantly improves the fatigue performance of the cushion rubber, extends tire service life, and improves driving safety and comfort. The strength-elongation and fatigue performance are increased by 10% and 17% respectively.
Smart Images

Figure CN120665354A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rubber tires, and in particular relates to a cushion rubber composition with high fatigue performance, a preparation method and an application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to those skilled in the art.
[0003] In all-steel radial tires, the cushion rubber plays a crucial role in the tire structure. During tire motion, the cushion rubber in the ground contact area becomes the primary load-bearing zone for shear stress between the tread and the cord ply, with deformation reaching 15-18% of the static value. This is the most complex transition zone in the tire, effectively absorbing and dissipating impact energy transmitted from the tread during driving, reducing cord fatigue.
[0004] Cushion rubber fatigue performance is a key factor in determining tire lifespan and safety. Inadequate cushion rubber fatigue performance can easily lead to tire defects such as interface delamination, stress crack propagation, and belt misalignment. Cushion rubber fatigue performance also directly impacts tire service life. High-quality cushion rubber can increase tire mileage by 20%-30%. Reduced cushion rubber fatigue performance also diminishes the tire's safety protection capabilities, resulting in decreased cushioning force and a vibration amplification effect. Therefore, improving cushion rubber fatigue performance is crucial for tire lifespan, driving safety, and comfort. Summary of the Invention
[0005] In order to address the deficiencies of the prior art, the present invention aims to provide a cushion rubber composition with high fatigue performance, a preparation method thereof, and an application thereof, which can improve the fatigue performance of the cushion rubber formulation.
[0006] In a full-steel radial tire, the cushion rubber plays three key roles in the tire structure: 1) Maintaining belt flatness and preventing sudden stress increases caused by direct contact between the tire body and the belt edge; 2) Distributing stress in the shoulder area, buffering shear forces between the belt and the tire body; and 3) Optimizing driving performance by balancing the stiffness difference between the tread and the tire body, reducing circumferential deformation at high speeds and improving handling stability. The cushion rubber of a full-steel radial tire is a core component of the tread-belt-carcass collaborative load-bearing system. Fatigue failure of the cushion rubber can lead to structural instability, performance degradation, and safety risks. Therefore, improving the fatigue performance of the cushion rubber is crucial for tire life, driving safety, and comfort.
[0007] In radial tire cushion rubber formulas, carbon blacks such as N660, N550, N774, and N375 are commonly used alone or in combination for reinforcement. Due to its good dynamic durability and processing dispersibility, N326 carbon black is mainly used in cord rubber, sidewall rubber, and part of the tread in all-steel radial tires. The present invention uses N326 as the main reinforcing carbon black in the cushion rubber in combination with a hydrazide compound. By using high-precision / purity N326 carbon black and adjusting the formula components, the fatigue performance of the cushion rubber formula is improved. The use of high-precision / purity N326 will increase the heat generation of the formula, resulting in a decrease in its fatigue performance. The complex formed by the hydrazide compound and zinc oxide can stabilize the cross-linking bonds and cross-linking density, avoiding degradation and fatigue performance degradation caused by heat accumulation during repeated movement of the rubber.
[0008] The three key elements of carbon black reinforcement are structure, particle size, and surface activity; structure and particle size are of primary concern. Heat generated during tire movement accelerates rubber degradation, so improving the fatigue performance of cushion rubber components requires consideration of heat generation. The present invention adjusts the following parameters for N326 carbon black for use in this solution: (1) Compressed DBP oil absorption value: The compressed DBP oil absorption value is usually used to characterize the structure of carbon black particles. The higher the compressed DBP oil absorption value, the higher the carbon black structure. High-structure carbon black improves the fatigue resistance of the rubber compound through the three-dimensional network structure during the mixing process. At the same time, high structure can also reduce the aggregation of carbon black particles and improve the dispersion, which improves the uniformity of the mixed rubber, thereby reducing stress concentration points and delaying crack propagation; improving the fluidity of the rubber compound and reducing fatigue failure caused by internal defects.
[0009] (2) CTAB adsorption value: CTAB adsorption value is usually used to characterize the specific surface area of carbon black ions. The higher the specific surface area of carbon black particles, the larger the contact area between carbon black and rubber molecular chains, and the stronger the bonding force between the two, thereby improving the tensile strength and tear resistance of the product, that is, improving the service life of the product. However, when the specific surface area of carbon black particles is too high, the degree of hindrance to the movement of the product molecular chain will be aggravated, causing high hysteresis loss and heat generation effect, which will have a negative impact on the fatigue performance of the product. Therefore, it is necessary to control the CTAB value within a smaller fluctuation range to avoid instability of product performance due to excessive fluctuation of the specific surface area of carbon black particles.
[0010] (3) Ash content: Usually used to characterize the purity of carbon black; metal impurities in ash can accelerate rubber aging and degradation, reducing the fatigue performance of the product. Reducing the ash content in N326 carbon black can effectively avoid the degradation of product fatigue performance caused by metal impurities.
[0011] In summary, compared to the technical specifications of conventional N326 carbon black, this solution achieves microstructural control by increasing its compressed DBP oil absorption, narrowing its CTAB adsorption range, and reducing its ash content. Furthermore, a complex formed by a hydrazide compound and zinc oxide enhances crosslinking stability and improves fatigue resistance. This solution, when applied to the formulation of rubber cushion components and fine-tuned with other components, achieves a comprehensive improvement in fatigue performance.
[0012] In order to achieve the above object, the technical solution of the present invention is: In a first aspect, the present invention provides a high fatigue performance cushion rubber composition comprising the following components by weight: 100 parts of natural rubber, 25-40 parts of N326 carbon black, 5-15 parts of white carbon black, 1-3 parts of oil, 1-3 parts of resin, 0-1 part of hydrazide compound, 1-2 parts of stearic acid, 3-8 parts of zinc oxide, 1.5-4 parts of antioxidant, 1-3 parts of adhesive, 1.0-1.5 parts of resorcinol, 2-4 parts of sulfur, 1-1.7 parts of accelerator, 0.05-0.2 parts of scorch retarder; In N326 carbon black, the compressed DBP oil absorption value is 75±2 cm 3 / 100g, CTAB adsorption specific surface area is 82±2m 2 / g, ash content is ≤0.2%.
[0013] In order to obtain better technical effects, in one or more embodiments, the high fatigue performance cushion rubber composition comprises the following components by weight: 100 parts of natural rubber, 25-40 parts of N326 carbon black, 5-15 parts of white carbon black, 1-3 parts of oil, 1-3 parts of resin, 0.1-1 parts of hydrazide compound, 1-2 parts of stearic acid, 3-8 parts of zinc oxide, 1.5-4 parts of antioxidant, 1-3 parts of adhesive, 1.0-1.5 parts of resorcinol, 2-4 parts of sulfur, 1-1.7 parts of accelerator, and 0.05-0.2 parts of scorch retarder.
[0014] In order to further obtain better technical effects, in one or more embodiments, the high fatigue performance cushion rubber composition comprises the following components by weight: 100 parts of natural rubber, 35-40 parts of N326 carbon black, 5-10 parts of white carbon black, 1-1.5 parts of oil, 1.5-2.5 parts of resin, 0.5-1 part of hydrazide compound, 1.5-2 parts of stearic acid, 3-4 parts of zinc oxide, 2-2.5 parts of antioxidant, 1-2 parts of adhesive, 1.0-1.2 parts of resorcinol, 2-3 parts of sulfur, 1.2-1.6 parts of accelerator, and 0.05-0.1 part of scorch retarder.
[0015] In order to further optimize the technical effect, the high fatigue performance cushion rubber composition contains the following components by weight: 100 parts of natural rubber, 37-39 parts of N326 carbon black, 7-9 parts of white carbon black, 1.1-1.3 parts of oil, 1.9-2.1 parts of resin, 0.7-0.9 parts of hydrazide compound, 1.9-2 parts of stearic acid, 3.5-3.7 parts of zinc oxide, 2-2.1 parts of antioxidant, 1-1.5 parts of adhesive, 1.0-1.1 parts of resorcinol, 2.3-2.5 parts of sulfur, 1.3-1.5 parts of accelerator, and 0.09-0.1 parts of scorch retarder.
[0016] In the formulation with natural rubber as the colloid, N326 mainly plays a reinforcing role. After cross-linking through vulcanization, accelerators, etc., the physical properties of the mixed rubber can be improved. In addition to its reinforcing effect, silica also forms a "methylene white bonding system" with resorcinol and adhesive RA / HMT, that is, the methylene donor (RA / HMT) reacts chemically with resorcinol at the vulcanization temperature to generate a phenolic resin adhesive with continued reaction ability. This substance has a three-dimensional resin network structure that penetrates the rubber matrix and anchors the surface of the skeleton material. In this process, silica participates in the above reaction as an adhesion promoter; the complex formed by the hydrazide compound and zinc oxide can stabilize the cross-linking bonds and cross-linking density.
[0017] In one or more embodiments, the natural rubber is one or more of SRT20 compound, SMR20 compound, TSR9710, and SVR3L compound.
[0018] In one or more embodiments, the white carbon black is one or more of SILICA HD175MP, TL-175MP, VN3GR, and rice husk ash white carbon black.
[0019] In one or more embodiments, the oil is one or more of TDAE oil, MES mineral oil, and environmentally friendly aromatic oil TUDALEN5244.
[0020] In one or more embodiments, the resin is one or more of tert-octylphenol formaldehyde resin SL-1801 / SP1068, hydrocarbon resin mixed resin 40MSF / RH100, and tackifying resin SL-1410.
[0021] In one or more embodiments, the hydrazide compound is DC-01, with the molecular formula: .
[0022] In one or more embodiments, the antioxidant is two or more of antioxidant RD, antioxidant 4020, and antioxidant DTPD.
[0023] In one or more embodiments, the adhesive is one or more of adhesive RA or HMT.
[0024] In one or more embodiments, the accelerator is one or more of accelerator NS, accelerator CZ, accelerator DZ, accelerator DM, and accelerator DPG80.
[0025] In one or more embodiments, the sulfur is OT20, has an oil content of 5±1.5%, a total sulfur content of 80.0±1.5%, and a thermal reduction of ≤25%. The scorch retarder may be CTP.
[0026] In a second aspect, the present invention provides a method for preparing the above-mentioned cushion rubber composition with high fatigue performance, comprising the following steps: adopting a two-stage mixing process to obtain the cushion rubber composition.
[0027] In one or more embodiments, in a first mixing stage, natural rubber, N326 carbon black, white carbon black, resin, hydrazide compound, stearic acid, zinc oxide, antioxidant and resorcinol are mixed and mixed for 30-40 seconds, then the bolt is raised, the speed is 35-45 rpm, oil is added, the bolt is pressed for 20-30 seconds, the bolt is raised and maintained for 10-20 seconds, the speed is 25-35 rpm, the bolt is pressed again, and mixing is carried out for 15-35 seconds, and mixing is carried out to 150-160° C. to obtain a masterbatch, which is then stored for 4-10 hours for standby use; In the final refining, a masterbatch, sulfur, accelerator, adhesive and scorch retarder are mixed and mixed for 25-35 seconds, the plug is raised and pressed, and the mixing is continued for 25-35 seconds, the plug is raised, the speed is 15-25rpm, the plug is pressed, and the mixing is continued until the temperature is 95-110℃ and the rubber is discharged.
[0028] It should be noted that the hydrazide compound needs to be added at the same time as zinc oxide to facilitate the formation of a complex between the two; if the two are not added together (i.e., the hydrazide compound and carbon black are added first, but zinc oxide is not added), the hydrazide compound will react with the carbon black and rubber, and even if zinc oxide is added later, the desired complex cannot be formed.
[0029] In one or more embodiments, in the first stage of mixing, before adding the material, the rotation speed is 40-50 rpm, the water temperature in the three zones (mixing chamber, rotor, discharge door) is 35±5° C., and the upper push bolt pressure is 5-6 MPa.
[0030] In one or more embodiments, during the final refining, before adding the material, the rotation speed is 20-35 rpm, the water temperature in the three zones (mixing chamber, rotor, discharge door) is 30±5° C., and the upper push bolt pressure is 4-5 MPa.
[0031] In a third aspect, the present invention provides the use of the above-mentioned cushion rubber composition with high fatigue performance in tires, preferably in radial tires.
[0032] One or more of the above technical solutions have the following advantages or beneficial effects: (1) Compared with the technical indicators of conventional N326, the present invention achieves control of the microstructure of N326 by improving the compressed DBP oil absorption value of N326, narrowing the range of CTAB adsorption value, and reducing the ash content; further combining the complex formed by hydrazide compound and zinc oxide to enhance the stability of cross-linking bonds and improve fatigue resistance, and applying it to the formulation of cushion rubber parts, combined with fine-tuning of other components of the formulation, to achieve a comprehensive improvement in its fatigue performance.
[0033] (2) In the high fatigue performance cushion rubber composition provided by the present invention, when the compressed DBP oil absorption value of N326 carbon black is 75cm 3 / 100g, CTAB value is 82m 2 / g, and when the ash content is 0.2%, the strength-elongation product and fatigue properties are improved the most, by 10% and 17% respectively, while other mechanical properties and thermal properties remain unchanged. Considering the carbon black cost and mixing energy efficiency, the compressed DBP oil absorption value of N326 / (cm 3 / 100g), CTAB adsorption value / (m 2 When the content of cellulose acetate (IMPA) and cellulose ether (IMPA) is controlled at 75±2%, 82±2%, and ≤0.2%, respectively, and the DC-01 additive is used in combination with the present invention, a cushion rubber composition with high fatigue performance can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The accompanying drawings, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0035] Figure 1 This is a sample before the tensile fatigue test in an embodiment of the present invention; Figure 2 This is a sample after tensile fatigue testing according to an embodiment of the present invention. DETAILED DESCRIPTION
[0036] Explanation of terms involved: A radial tire is a tire structure designed with the carcass cords arranged in a radial direction (perpendicular to the rolling direction, i.e., arranged at 90° radially). Its core characteristic is the tightening effect of the belt on the carcass. Compared to bias tires, radial tires offer significantly improved wear resistance, service life, rolling resistance, load capacity, and comfort. Radial tires are a major trend in tire design and development.
[0037] Cushion rubber: In the radial tire structure, it is located between the carcass cord layer and the edge end of the belt layer, extending upward to below the tread basic rubber, and has a strip or special-shaped structure. Fatigue performance: refers to the ability of a material or component to resist damage accumulation under cyclic loads. Its essence is a key indicator for evaluating dynamic durability. DBP oil absorption value: The volume of dibutyl phthalate (DBP) absorbed by 100g of carbon black under standard conditions (unit: mL / 100g), which is used to characterize the structural density and dispersion of carbon black aggregates.
[0038] Compression DBP value: The DBP oil absorption value of carbon black after compression under high pressure (24MPa) reflects the stability of the carbon black structure.
[0039] CTAB adsorption value: The surface area of carbon black measured by cetyltrimethylammonium bromide (CTAB) adsorption method (unit: m 2 / g), characterizes the actual contact interface between carbon black and rubber, and can usually be used to characterize the particle size / specific surface area of carbon black particles.
[0040] Ash content: the mass percentage of inorganic residues (such as metal oxides, silicates, etc.) in carbon black.
[0041] In the present invention, unless otherwise specified, other test materials and instruments and equipment are conventional test materials in this field and can be purchased through commercial channels.
[0042] Conventional N326 refers to a commonly used product on the market. In the embodiments (N326-1, N326-2, N326-3, N326-4, N326-5, N326-6, and N326-7), only three parameters of N326 (compressed DBP oil absorption value, CTAB adsorption specific surface area, and ash content) are limited. As long as these three parameter indicators (compressed DBP oil absorption value, CTAB adsorption specific surface area, and ash content) meet the requirements of the present invention, other parameter indicators are not specially limited as long as they meet the general industry standards.
[0043] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0044] Example 1 Mixing preparation steps: (1) Mixing in one stage: the rotor speed is 45 rpm, the water temperature in the three zones (mixing chamber, rotor, discharge door) is 35±5℃, the upper plug pressure is 5.5 MPa, the above-mentioned natural rubber, carbon black, white carbon black, chemicals (except sulfur, adhesive, accelerator, anti-scorching agent, oil) are added to the internal mixer and mixed for 35 seconds, then the plug is raised, the rotor speed is 40 rpm, the oil is added, the plug is pressed for 25 seconds, the plug is raised and kept for 10 seconds, the rotor speed is 30 rpm, the plug is pressed again, and mixing is carried out for 15 seconds, and mixing is carried out to 152℃ for rubber discharge to obtain a masterbatch, which is parked for 4-10 hours for use.
[0045] (2) Final refining: rotor speed 20-35 rpm, three-zone water temperature (mixing chamber, rotor, discharge door) 30±5℃, upper bolt pressure 4.5 MPa, add a masterbatch, sulfur, accelerator, adhesive, and anti-scorch agent into the internal mixer, mix for 30 seconds, raise the bolt, press the bolt, mix for 30 seconds, raise the bolt, rotor speed 20 rpm, press the bolt, mix to 102℃ and discharge, and obtain a tire cushion rubber composition mix.
[0046] The contents and components of the high fatigue performance cushion rubber composition are shown in Table 1.
[0047] Table 1
[0048] The specific technical indicators of N326 carbon black in the above embodiment are shown in Table 2.
[0049] Table 2
[0050] Comparative Example 1 and Example 8 used conventional N326 carbon black, and the carbon black used in Examples 1-7 and 9 was N326 with adjusted indicators such as structure, specific surface area, and ash content.
[0051] The present invention measures the properties of the rubber mixes prepared in the above examples. The test items include mechanical property evaluation, heat generation performance evaluation, and fatigue performance evaluation. The evaluation method is as follows: (1) Mechanical properties evaluation: The tensile stress and tensile properties were tested according to GB / T528-2009, and the tear properties were tested according to GB / T528-2008. The aging test involved placing the sample in an aging chamber for 24 hours at 100°C and then taking it out for testing.
[0052] The values of Examples 1-7 and Comparative Example 1 are all expressed as indexes, and the values of the tensile stress, strength-elongation product, and tear strength of Comparative Example 1 are set to 100. The larger the value, the better the relevant performance.
[0053] (2) Fatigue performance evaluation: The test is carried out in accordance with the GB / T1688-2008 method. The aging test is to place the sample in an aging box for hot air aging at 100°C for 24 hours and then take it out for testing.
[0054] The values of Examples 1-7 and Comparative Example 1 are all expressed as indexes, with the number of comparative example tests set to 100. The larger the value, the better the fatigue performance.
[0055] (3) Evaluation of heat generation performance: The evaluation was performed using a rubber processing analyzer (RPA). The specific method was to set the temperature to 151°C, the strain to 7%, and the frequency to 1.67 Hz, and to achieve stable conditions for 2 minutes; the test was placed in a vulcanization chamber for 30 minutes; the temperature was then lowered to 60°C, the frequency was 10 Hz, and the strain was 7% for testing, with tanD selected as the evaluation indicator.
[0056] The values of Examples 1-7 and Comparative Example 1 are all expressed as indexes, with the tanD value of Comparative Example 1 being set to 100. The larger the value, the worse the heat generation performance.
[0057] The comparison of test data is shown in Table 3.
[0058] Table 3
[0059] From the test data in Table 3 above, we can see that: The test data of Comparative Example 1 and Examples 1-2 show that the compressed DBP oil absorption value of N326 carbon black particles is 75 cm 3 When the load is 100g, the strength-elongation product and fatigue properties are increased by 7% and 6% respectively, while other mechanical properties and heat generation properties do not change much. Moreover, the strength-elongation product and fatigue properties are kept in the best state after aging.
[0060] The test data of Comparative Example 1 and Examples 2-5 show that the CTAB value of N326 carbon black particles is 82m 2 / g, with other mechanical properties and heat generation properties not changing much, the strength-elongation product and fatigue properties are improved by 10% and 8% respectively, and the strength-elongation product and fatigue properties are maintained at the best state after aging.
[0061] The test data of Comparative Example 1 and Examples 5-7 show that when the ash content of N326 carbon black is 0.2%, the strength-elongation product and fatigue properties are improved by 15% and 17% respectively, while other mechanical properties and heat generation properties do not change much; and the strength-elongation product and fatigue properties are also maintained at the best state after aging.
[0062] The test data of Comparative Example 1 and Examples 7-9 show that the addition of DC-01 and an ash content of N326 of 0.2% further improves the strength-elongation product and fatigue properties to 14% and 16%, while improving the properties after aging to 15% and 25%, respectively.
[0063] In summary, when the compressed DBP oil absorption value of N326 carbon black is 75cm 3 / 100g, CTAB value is 82m 2 / g, when the ash content is 0.2%, the other mechanical properties and thermal properties do not change much, but the strength-elongation product and fatigue properties are improved the most, by 10% and 17% respectively. Considering the carbon black cost and mixing energy efficiency, the compressed DBP oil absorption value of N326 / (cm 3 / 100g), CTAB adsorption value / (m 2 When the content of cellulose acetate (IMPA) and cellulose ether (IMPA) is controlled at 75±2%, 82±2%, and ≤0.2%, respectively, and the DC-01 additive is used in combination with the present invention, a cushion rubber composition with high fatigue performance can be obtained.
[0064] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.
Claims
1. A high fatigue performance cushion rubber composition, characterized in that: The cushion rubber composition comprises the following components by weight: 100 parts of natural rubber, 25-40 parts of N326 carbon black, 5-15 parts of white carbon black, 1-3 parts of oil, 1-3 parts of resin, 0-1 part of hydrazide compound, 1-2 parts of stearic acid, 3-8 parts of zinc oxide, 1.5-4 parts of antioxidant, 1-3 parts of adhesive, 1.0-1.5 parts of resorcinol, 2-4 parts of sulfur, 1-1.7 parts of accelerator, 0.05-0.2 parts of scorch retarder; In N326 carbon black, the compressed DBP oil absorption value is 75±2 cm 3 / 100g, CTAB adsorption specific surface area is 82±2 m 2 / g, ash content is ≤0.2%.
2. The high fatigue performance cushion rubber composition according to claim 1, characterized in that: 100 parts of natural rubber, 25-40 parts of N326 carbon black, 5-15 parts of white carbon black, 1-3 parts of oil, 1-3 parts of resin, 0.1-1 parts of hydrazide compound, 1-2 parts of stearic acid, 3-8 parts of zinc oxide, 1.5-4 parts of antioxidant, 1-3 parts of adhesive, 1.0-1.5 parts of resorcinol, 2-4 parts of sulfur, 1-1.7 parts of accelerator, 0.05-0.2 parts of scorch retarder.
3. The high fatigue performance cushion rubber composition according to claim 2, characterized in that: 100 parts of natural rubber, 35-40 parts of N326 carbon black, 5-10 parts of white carbon black, 1-1.5 parts of oil, 1.5-2.5 parts of resin, 0.5-1 part of hydrazide compound, 1.5-2 parts of stearic acid, 3-4 parts of zinc oxide, 2-2.5 parts of antioxidant, 1-2 parts of adhesive, 1.0-1.2 parts of resorcinol, 2-3 parts of sulfur, 1.2-1.6 parts of accelerator, 0.05-0.1 part of scorch retarder.
4. The high fatigue performance cushion rubber composition according to claim 1, characterized in that: The natural rubber is one or more of SRT20 compound, SMR20 compound, TSR9710, and SVR3L compound; The white carbon black is one or more of SILICA HD175MP, TL-175MP, VN3GR, and rice husk ash white carbon black; The oil is one or more of TDAE oil, MES mineral oil, and environmentally friendly aromatic oil TUDALEN5244; The resin is one or more of tert-octylphenol formaldehyde resin SL-1801 / SP1068, hydrocarbon resin mixed resin 40MSF / RH100, and tackifying resin SL-1410; The hydrazide compound is DC-01, and its molecular formula is: 。 5. The high fatigue performance cushion rubber composition according to claim 1, characterized in that: The antioxidant is two or more of antioxidant RD, antioxidant 4020, and antioxidant DTPD; The adhesive is one or more of adhesive RA or HMT; The accelerator is one or more of accelerator NS, accelerator CZ, accelerator DZ, accelerator DM, and accelerator DPG80; The sulfur is OT20, with an oil content of 5±1.5%, a total sulfur content of 80.0±1.5%, and thermal reduction ≤25%.
6. A method for preparing the high fatigue performance cushion rubber composition according to any one of claims 1 to 5, characterized in that: The following steps are involved: The product is obtained by adopting a two-stage mixing process.
7. The preparation method according to claim 6, characterized in that In the first stage of mixing, natural rubber, N326 carbon black, white carbon black, resin, hydrazide compound, stearic acid, zinc oxide, antioxidant and resorcinol are mixed and mixed for 30-40 seconds, then the plug is raised, the speed is 35-45 rpm, oil is added, the plug is pressed for 20-30 seconds, the plug is raised and kept for 10-20 seconds, the speed is 25-35 rpm, the plug is pressed again, and mixing is carried out for 15-35 seconds. The mixing is continued until the temperature reaches 150-160° C. and the rubber is discharged to obtain a first stage masterbatch, which is then stored for 4-10 hours for standby use; Preferably, in the first stage of mixing, before adding the materials, the rotation speed is 40-50 rpm, the water temperature in the three zones is 35±5° C., and the upper push bolt pressure is 5-6 MPa.
8. The preparation method according to claim 6, characterized in that In the final mixing, a masterbatch, sulfur, accelerator, adhesive and scorch retarder are mixed and mixed for 25-35 seconds, the plug is raised and pressed, and the mixing is continued for 25-35 seconds, the plug is raised, the rotor speed is 15-25rpm, the plug is pressed, and the mixing is continued until the temperature is 95-110℃ and the rubber is discharged.
9. The preparation method according to claim 6, characterized in that During the final refining, before adding the material, the rotor speed is 20-35rpm, the water temperature in the three zones is 30±5℃, and the upper bolt pressure is 4-5Mpa.
10. Use of the high fatigue performance cushion rubber composition according to any one of claims 1 to 5 or the high fatigue performance cushion rubber composition obtained by the preparation method according to any one of claims 6 to 9 in a tire.
Citation Information
Patent Citations
Low-heat-generation and high-thermal-conductivity tire base rubber composition and mixing method thereof and tire
CN113652012A
Rubber composition for tires, mixing method and application
CN117004098A
Laminated tread cushion rubber composition
CN1850894A
Rubber composition and heavy-load pneumatic tire using the same
JP2004189772A
Rubber composition for tire improved anti-fatigueproperty
KR1020030095080A